2011
DOI: 10.1371/journal.pone.0028310
|View full text |Cite
|
Sign up to set email alerts
|

Cultivation of Human Corneal Endothelial Cells Isolated from Paired Donor Corneas

Abstract: Consistent expansion of human corneal endothelial cells (hCECs) is critical in the development of tissue engineered endothelial constructs. However, a wide range of complex culture media, developed from different basal media have been reported in the propagation of hCECs, some with more success than others. These results are further confounded by donor-to-donor variability. The aim of this study is to evaluate four culture media in the isolation and propagation of hCECs isolated from a series of paired donor c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
158
0
5

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 135 publications
(164 citation statements)
references
References 18 publications
1
158
0
5
Order By: Relevance
“…n = 4, *p < 0.01, and **p < 0.05. Primary CECs were cultivated using the dual media approach to the third passage and characterized for their expression of known markers indicative of the corneal endothelium such as (B) sodium-potassiumtransporting adenosine triphosphatase (Na and expressed higher levels of corneal endothelium-specific genes ATP1A1, SLC4A11 and COL8A1, as well as reported cellular markers of the corneal endothelium (11,44).…”
Section: Characterization Of Cultivated Human Corneal Endothelial Celmentioning
confidence: 99%
“…n = 4, *p < 0.01, and **p < 0.05. Primary CECs were cultivated using the dual media approach to the third passage and characterized for their expression of known markers indicative of the corneal endothelium such as (B) sodium-potassiumtransporting adenosine triphosphatase (Na and expressed higher levels of corneal endothelium-specific genes ATP1A1, SLC4A11 and COL8A1, as well as reported cellular markers of the corneal endothelium (11,44).…”
Section: Characterization Of Cultivated Human Corneal Endothelial Celmentioning
confidence: 99%
“…The first is based on the use of enzymes such as collagenase, trypsin, or dispase. 73,74 This technique has the tendency of leading to cellular degradation due to the incubation time required to detach cells from the matrix, and because it also allows for the dissociation of the collagen matrix in which the keratocytes are located. Additionally, it often results in contamination from the stromal cells.…”
Section: Cell Therapymentioning
confidence: 99%
“…72 In addition, a recent study concluded that a culture media that combines EGF, insulin, transferrin, bFGF, NGF, and pituitary extract promotes proliferative capacity up to the third passage. 73 In order to replicate the monolayer of the corneal endothelium, there have been developments to maintain cell morphology, density, and function. Materials like collagen, amniotic membrane, and biodegradable polymers have successfully been used in culture media and animal models.…”
Section: Cell Therapymentioning
confidence: 99%
“…The peel-and-digest method by Peh et al [20] has resulted in successful cultures. Other methods include stripping or bubble techniques to separate the Descemet's membrane from the stroma and then digestion of the cells using trypsin for cell culture.…”
Section: Isolation Of Human Corneal Endothelial Progenitors Single Cementioning
confidence: 99%